Penile Ewing's Sarcoma - A Rare Entity. (9th November 2022) - kaur, J; Banerjee, N
Abstract: Introduction/Objective: Ewing sarcoma is a cancer involving the bones or the tissue around bones. It is the second most common malignant bone tumour comprising 10-15% of all primary bone tumours, most commonly affecting children and young adults. It can also be seen in adults also. Males are more commonly affected then females. Any bone can be affected but the lower extremity, the pelvis, upper extremity, axial skeleton and ribs, and face cases. Similar histology tumours when seen in soft tissue are peripheral primitive neuroectodermal tumour (pPNET), neuroepithelioma, and Askin tumour. It is always difficult to know the primary site when soft tissues are involved as it can be infiltration from bone or from soft tissue to bone. Penis is least common site involved with Ewing's sarcoma in young male. Methods/Case Report: This is a case report of a 22 year old male with penile lesion. He presented with the chief complaints of mass at the shaft of penis. The partial penectomy specimen was received along with the bilateral inguinal lymph node. On gross there was a ulcero-proliferative growth. Results (if a Case Study Enter NA): On histopathological examination showed small blue round cell tumour and further immunohistochemistry with CD99 and NKX2.2 revealed the diagnosis of Ewing's sarcoma, however lymph nodes showed reactive lymphoid hyperplasia. Conclusion: The Ewing sarcoma at the penile region is rarest entity. Only 7 cases are reported worldwide. The imaging modalities like CT or MRI can be used to know the extension. The diagnosis is primarily based on morphological features, immunohistochemical analysis and translocation analysis. However it is important to find out if any other soft tissue site is involved. The important prognostic markers are presence and absence of metastasis, size of tumour, necrosis and presence of fusion transcripts.